2013
DOI: 10.1007/s00392-013-0572-3
|View full text |Cite
|
Sign up to set email alerts
|

Invasive versus non-invasive cooling after in- and out-of-hospital cardiac arrest: a randomized trial

Abstract: Invasive cooling has advantages with respect to temperature management over surface cooling; however, did not result in different outcome as measured by NSE release in SCA survivors. Bleeding complications were more frequently encountered by invasive cooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 34 publications
6
63
0
Order By: Relevance
“…8,[11][12][13][14]24,[33][34][35] In our study, we failed to demonstrate a clear clinical superiority of the endovascular cooling versus basic external cooling for the management of OHCA patients, despite important differences in the induction and maintenance phases of TTM. According to the literature, the level of evidence to assess the superiority of intravascular cooling on the prognosis after CA remains poor.…”
Section: Downloaded From July 21 2015mentioning
confidence: 83%
See 3 more Smart Citations
“…8,[11][12][13][14]24,[33][34][35] In our study, we failed to demonstrate a clear clinical superiority of the endovascular cooling versus basic external cooling for the management of OHCA patients, despite important differences in the induction and maintenance phases of TTM. According to the literature, the level of evidence to assess the superiority of intravascular cooling on the prognosis after CA remains poor.…”
Section: Downloaded From July 21 2015mentioning
confidence: 83%
“…13 Conversely, 3 other studies comparing endovascular with surface cooling methods found no significant difference in survival with good neurological outcome after a CA. 10,11 However, the time from CA to achieving TH was similar for both devices in 2 of these studies, 10,14 whereas the number of patients enrolled was rather limited, 11,14 leading to debatable conclusions about its potential clinical impact. Finally, most human studies found results similar to ours when several other devices were used to early achieve TH, especially with cold intravenous fluids.…”
Section: Downloaded From July 21 2015mentioning
confidence: 97%
See 2 more Smart Citations
“…Two Class III studies compared different invasive vs superficial cooling methods. 29,30 An additional Class III study 31 investigated the effect of a standardized treatment protocol. Because single Class III studies cannot drive recommendations, details of these studies are discussed only in the complete guideline.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%